Focus on Followers: An Analysis of Factors Impacting Division I Athletes’ Name, Image, and Likeness Value - Sarah Stokowski; Chris Corr; Andrew Rudd; Imani Lewis; Adria Powell; Abigail Stuart; Sydney Bellamy; Jaylen Rivers; Michael Godfrey (Journal of Applied Sports Management, 2024)
Opportunities to engage in name, image, and likeness (NIL) partnerships have pervaded college athletics on numerous fronts. To contextualize the most important factors contributing to a college athletes’ NIL value, the present study analyzed High-Major basketball players NIL valuations during the 2023-2024 season. In total, data representing 69% of High-Major men’s basketball players (n = 572) and 52% of High-Major women’s basketball players (n = 429) was collected. Attempting to statistically control for factors such as institutional prestige, media exposure, and athletic performance, results indicate that an athlete’s social media following – specifically their Instagram following – is the most determinant factor contributing to their NIL valuation. While athletes, athletic administrators, and media pundits alike have suggested NIL may exist as antithetical to the fundamental nature of Title IX, the findings of this study indicate that sociocultural factors pertaining to social media users’ follow intentions may put women’s sport college athletes at a distinct advantage in potentially marketing their NIL.
Keywords: NCAA; college athletics; social media; athlete branding; gender